2016
DOI: 10.1016/j.hpb.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal liver metastases: disappearing lesions in the era of Eovist hepatobiliary magnetic resonance imaging

Abstract: Despite disappearance on Eovist MR imaging (the most sensitive available imaging modality), 38.5% of all colorectal metastases disappeared and of those, 55% were viable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 17 publications
1
37
0
Order By: Relevance
“…Contrast‐enhanced intraoperative ultrasonography (CE‐IOUS) has also been shown to provide significant information in intraoperative diagnosis . Although the efficacy of addition of these new imaging modalities to detect DLMs has been reported in several studies, it remains unclear how these available imaging modalities can be used effectively to detect DLMs after chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Contrast‐enhanced intraoperative ultrasonography (CE‐IOUS) has also been shown to provide significant information in intraoperative diagnosis . Although the efficacy of addition of these new imaging modalities to detect DLMs has been reported in several studies, it remains unclear how these available imaging modalities can be used effectively to detect DLMs after chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Despite a complete response on imaging, many studies have shown persistent viable tumor cells at the site of the "disappearing lesions". With a lesion based analysis, the incidence of disappearing lesions ranges from 11% to 36% of initially detected CRCLM, and half of these lesions can present persistent disease, which may have great impact on patient relapse as well as on survival (25)(26)(27).…”
Section: Ricardo Jorge Teixeira Martins and José Guilherme Lopes Rodrigmentioning
confidence: 99%
“…Nevertheless, visual servoing raises several limitations, in particular for the needle insertion: 1) Per-operative images usually offer poor visibility of internal structures (such as a tumor or vessels), and it is very challenging to extract essential data at high frequency. This is especially true for disappearing liver metastases: due to chemotherapy effects, the shape of tumors may change or they may become invisible in intraoperative images, even if the lesions still contain active tumors [4]. 2) When large deformations occur the control law of the robot can be significantly modified which is extremely difficult to relate with image-based displacements.…”
Section: Introductionmentioning
confidence: 99%